Enterprise skills and training needs of postgraduate research students. Issue 8 (4th November 2014) - Smith, Kelly; Williams, Dina; Yasin, Naveed; Pitchford, Ian
Abstract : Purpose: – The purpose of this paper is to present a survey of postgraduate research (PGRs) students studying at the University of Huddersfield, concentrating on entrepreneurial attributes and the importance of enterprise-related skills future career intentions. Design/methodology/approach: – Electronic survey questions asked respondents to rate their confidence in a series of enterprise-related skills, and each skill's importance in their career development. Identification with attributes relating to independence, risk taking, self-efficacy, tolerance of ambiguity, and innovativeness were explored. Further questions probed the importance of enterprise skills development, research impact, and career aspirations including business start-up potential. Findings: – Respondents identified with entrepreneurial attributes and were positive towards enterprise skills development. The majority felt that their research could have commercial impact, and over a third reported that starting a business appealed to them. Comparisons of importance and confidence ratings identified skills areas where confidence was relatively low and needed to be improved, where there is a large gap between confidence and importance, and where a skill was rated as having lower importance than is optimal from an institutional perspective. Interestingly, different groups of students considered "self-employment" compared with "business start-up" as a career option. Research limitations/implications: – These single-institution results suggest that PGRs are more entrepreneurial than might be expected. Is the higher education (HE) sector underestimating the entrepreneurial potential of the PGR population, their appetite for engaging in enterprise, and their enterprise and commercialisation training needs? Originality/value: – The results have relevance for the HE community in terms of understanding PGR entrepreneurial attributes, and training needs for enterprise and commercialisation of research output.